Common Histological Features Suggesting Enchondral Ossification Pathways in Calciphylaxis of Various Origins: A Study of Human Subcutaneous Tissue Biopsies - Simon Aberger; Barbara Findenig; Jane Beil; Nicole Aichinger; Josef Koller; Cees Vermeer; Leon Schurgers; Elke Theuwissen; Elena Moré; Michael Franzen; Cornelia Kronberger; Hermann Salmhofer (Medical Journals Sweden, 2023)
Calciphylaxis is a rare, yet underdiagnosed condition causing high mortality in patients with severe renal and cardiovascular disease. Since knowledge of the pathophysiology of calciphylaxis is limited, a differential analysis of histological alterations in patient subgroups with various comorbidities might expose different disease phenotypes and allow deeper insights into the pathophysiology of the condition. Histological markers of osteogenesis and calcification were investigated in a group of 18 patients with clinically and histologically verified calciphylaxis, using immunohistochemical staining. Analysis of staining intensity and distribution of marker proteins in histological structures was performed to evaluate distinct patterns between subgroups with different clinical comorbidities in comparison with a control group. In all cases, immunohistochemical staining for bone matrix proteins, bone-morphogenic proteins and matrix-Gla proteins co-localized with subcutaneous vascular and interstitial calcifications. Significant expression of bone-morphogenic protein-7 and active matrix-Gla protein was observed. Mortality was associated with renal comorbidities and increased expression of bone-morphogenic protein-7. However, no distinct histological patterns were found between subgroups with renal disease, warfarin intake or coexisting micro- and macro-angiopathies. The upregulation of osteogenic markers (including bone-morphogenic protein-7) plays a major role in the development of calciphylaxis. Clinical outcome correlates with kidney function and phosphate handling, suggesting different pathophysiological mechanisms. However, biopsy  at late-stage disease shows a common histological phenotype, involving enchondral ossification.